0 Rajan@2021Guru Asked: March 16, 20212021-03-16T09:57:09+05:30 2021-03-16T09:57:09+05:30In: ICSE The sum of the first n terms of an A.P. is 3n2 + 6n. Find the nth term of this A.P. 0 It is given that the sum of the first n terms of an A.P. is 3n2+6n. Calculate the nth term of this A.P. ML Aggarwal Avichal Publication Arithmetic Progression Chapter 9 Question 16 arithmetic progressionicseml aggarwal Share Facebook 1 Answer Voted Oldest Recent MathsMentor Guru 2021-03-16T16:31:00+05:30Added an answer on March 16, 2021 at 4:31 pm sn=3n2+6n sn−1=3(n−1)2+6(n−1) sn−1=3(n2−2n+1)+6n−6 sn−1=3(n2−2n+1)+6n−6 sn−1=3n2−6n+3+6n−6 sn−1=3n2−3 tn=sn−sn−1 tn=3n2+6n−3n2+3 tn=6n+3 0 Reply Share Share Share on Facebook Share on Twitter Share on LinkedIn Share on WhatsApp Leave an answerLeave an answerCancel reply Featured image Select file Browse Add a Video to describe the problem better. Video type Youtube Vimeo Dailymotion Facebook Choose from here the video type. Video ID Put Video ID here: https://www.youtube.com/watch?v=sdUUx5FdySs Ex: "sdUUx5FdySs". Click on image to update the captcha. Save my name, email, and website in this browser for the next time I comment. Related Questions Question 1: Find the value of x for which (8x + 4), (6x – 2) and (2x + ... Problem 2: Find the indicated terms in each of the following sequences whose nth terms are(iii) an = ... Problem 1: Write the first terms of each of the following sequences whose nth term is: (i) an ... Ques (b) In the figure (ii) given below, O and O’ are centres of two circles touching each ... Question 39. (a) In the figure (i) given below, AB is a chord of the circle with centre ...

## sn=3n2+6n

sn−1=3(n−1)2+6(n−1)

sn−1=3(n2−2n+1)+6n−6

sn−1=3(n2−2n+1)+6n−6

sn−1=3n2−6n+3+6n−6

sn−1=3n2−3

tn=sn−sn−1

tn=3n2+6n−3n2+3

tn=6n+3